JOINT VIETNAMESE - RUSSIAN RESEARCHES IN MARINE BIOLOGY DURING 1980-2007 - An, Nguyen Tac; Dautova, T. N. (Vietnam Journal of Marine Science and Technology, 2008)
The main programs of cooperation between IMB FESC AS USSR and Institute of Marine Researches belonging to the National Centre of Natural Science and Technology in Vietnam for the period of 1980 - 2000 were established asfollows: - Tropical littoral ecosystems (coral reef and the intertidal area: biodiversity and productivity). - Biological basis for mariculture of algae and invertebrates. - Biochemistry and chemislly ofmarine organisms. - Microelemental consistency of mass species of algae and invertebrates. Co-researches in the 21th century are being held due to agreements of co-activities between IMB RAS and Scientific Institutes of VAST Together with Institute of Oceanography, Institute of Materials and Institute of Marine Environment and Resources. Institute of Natural Combinations’ Chemistty, of  VAST, there are some main cooperative projects: - Due to increasing influence of anthropogenic stress if was concluded that importan task is to use macrophytes and reef building corals as indicators of anthropogenic pollution. Another idea - to estimate productive resources of marine algae, grasses and reef building corals, their realization in nature and cultivation. - Research in spheres of biodiversity of Vietnamese open waters. - Study of bioactive substances of marine animals and algae. - Study of species diversity and distribution of marine plants in southern and northern regions of Vietnam.